Impact of layering, sequencing, and integration approaches in mitigating food and nutrition insecurity in Zimbabwe - Nomagugu Ndlovu; Clayton Mafuratidze (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
The reduction in food production due to climate shock has contributed to food and nutrition insecurity, malnutrition, and diet-related non-communicable diseases. There is an urgent need for adaptation measures to manage the impact of climate change on communities. Developing resilience in food and nutrition security remains a novel concept. The aim of the study was to determine the impact of Layering, Sequencing and Integration (LSI) of different interventions on food and nutrition outcomes among smallholder farmers. Participants were drawn from three wards in the Zvishavane District of the Midlands province in Zimbabwe. A total of 301 randomly chosen participants were interviewed. A mixed methodology using quantitative and qualitative tools was used to collect the data. The majority (95,3%) of the study participants had an acceptable diet based on the food consumption score (77,1%), with a high dietary diversity score, and 48,2% had an annual cereal surplus. A total of 69,1% of participants had no reduced coping strategies. Economic shocks (34,9%) were most severe, followed by climate-induced shocks (24,6%). The LSI approach can potentially increase diversified food production levels, thereby increasing access to diverse foods and resulting in improved food and nutrition security outcomes for a given community.